Raman fiber laser with highly non-linear fiber - Zainol Abidin, Nadiah; Abu Bakar, Muhammad Hafiz; Mahdi, Mohd Adzir; Tamchek, Nizam (IEEE, 2014)
This paper demonstrates the power performance of an asymmetrical distributed feedback Raman fiber laser (DF-RFL) employing 2 km of highly nonlinear fiber (HNLF). The forward-pumped architecture exhibited better threshold condition and higher output power alongside a broader spectral profile compared to a DF-RFL utilizing a standard transmission fiber. This experimental layout could offer better insight on flatter broadband gain compared to conventional DF-RFL.